A Law Firm Librarian's Guide to KM. (26th September 2016) - Russell, Hélène
Abstract: This article is written by Hélène Russell, author and teacher in the field of legal sector Knowledge Management. It presents an easy to read foundation level guide to legal sector Knowledge Management for law firm Information Professionals. It explains what Knowledge is, what Knowledge Management (KM) is, how it differs from Information Management (IM) and how law firm Information Professionals can expand their roles to help their organisations meet business goals through strategic KM as well as IM, or manage an imposed transition from IM to IM+KM.